Structure and mechanical behavior of dentin-inspired nanoporous copper. (February 2020) - Ibru, Timothy; Violante, Sarah; Vennat, Elsa; Arson, Chloé; Antoniou, Antonia
Abstract: Dentin possesses a hierarchical porous structure with varying cross-scale morphology and characteristic lengths ranging from nanometers to micrometers. Nanoporous (NP) Copper is fabricated with nano-sized and micron-sized features that mimic dentin's morphology. NP Copper Young's modulus, hardness, and plastic Poisson's ratio are shown to be in the range characteristic of dentin. This correspondence in properties may allow use of NP metals to advance tooth restoration techniques by using them as model systems to study infiltration of dentin with resins. Moreover, the multi-scale porosity may inspire design of 3D catalysts with efficient reactant mass transport through the catalyst volume. Graphical abstract: Image, graphical abstract